Synthesis and Antiviral Studies of Novel N-Sulphonamidomethyl piperazinyl Fluoroquinolones - Selvam, P. (Medknow Publications, 2009)
A series of novel N-Sulphonamidomethyl piperzinyl fluoroquinolones were synthesized and screened antiviral activity. Eight compounds were synthesized through modifying the N(4)-hydrogen of piperazine in fluoroquinolones with formaldehyde and sulphanomides by Mannich reactions. The structures of the synthesized compounds were characterized by means of their IR and (1)H-NMR spectral data. Synthesized compounds were screened for antiviral activity against influenza A (H1N1, H3N2, H5N1) and influenza B viruses in MDCK cell culture. The antiHIV activities of the new compounds were screened for antiviral activity against replication of HIV-1(III(B)) in MT-4 cells. Cytotoxicity of the synthesized compounds was also tested in mock-infected MDCK and MT-4 cells. Compound CF-SD and CF-SDM inhibits the influenza A (H1N1) and compound GF-SDM inhibit the replication of influenza A (H5N1) and B in MDCK cells. All compounds displayed cytostatic propertity in MT-4 cells. Among the compounds tested, GF-SDM (CC(50)=39.44 μM) most toxic compound in this series.